Application and limitation of molecular data and essential oil content in identification of Leutea elbursensis Mozaff in northern Iran - Emami-Tabatabaei, Samane Sadat; Larijani, Kambiz; Mehregan, Iraj (Acta Botanica Croatica, 2018)
In this paper, the internal transcribed spacer (ITS) sequences, genetic structure and the chemical composition of essential oils of four populations belonging to Leutea elbursensis and Leutea petiolaris, two species endemic to northern Iran, are analyzed. Phylogenetic analysis based on the ITS data showed that all accessions of L. elbursensis formed a monophyletic clade, and L. elbursensis was a sister to the rest of Leutea species. Results of amplified fragment length polymorphism (AFLP) analysis performed on the total genome showed that all individuals presented in the study belonged to two different genetic clusters. The individuals belong to L. petiolaris had a different genetic structure and yielded no traceable amount of essential oils. The essential oil obtained from the ripe fruits of L. elbursensis yielded 0.5–0.6% of volatile essential oils. In total, 15–29 volatile natural components were identified on the basis of their mass spectra characteristics and retention indices, in which alpha-pinene (33.18–43.22%), beta-pinene (32.4–40.9%) were the major constituents. Our results indicate that L. elbursensis is a distinct species, segregated from the other species based on morphology, ITS data and AFLP profile. In addition, despite the relatively uniform genetic structure of L. elbursensis, the chemical composition of essential oil could be highly affected by different factors.